Pemberdayaan Masyarakat Berbasis Penyusunan Laporan Keuangan Sederhana Pada Kelompok Tani Hutan di Kelurahan Marikurubu: Community Empowerment Based on The Preparation of Simple Financial Statements on Forest Farmer’s Group in Marikurubu Village - Fatmawati Kaddas; Firlawanti Lestari Baguna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The problem that becomes an obstacle in the captive/breeding business has limited capital. The service implementation aims to provide knowledge and training related to the management of financial statements because it has not used a recording system that describes valid financial conditions for decision-making. The results of the activity were expected that participants could understand and know the importance of recording financial statements simply so that they can calculate the income earned in running a business and avoid the risks that will arise. These financial statements were recorded to motivate the public to improve their abilities and build large-scale businesses.